Factors for Visual Acuity Improvement After Anti-VEGF Treatment of Wet Age-Related Macular Degeneration in China: 12 Months Follow up - Lu, Yan; Huang, Wenzhi; Zhang, Yuehong; Huang, Xiongfei; Zhang, Xu; Ma, Haizhi; Ren, Guoliang; Shi, Feng; Kuang, Lihui; Yan, Shigang; Luo, Shuke; Zhang, Junyan; et al. (Frontiers in Medicine, 2021)
Purpose: To evaluate the treatment solutions and efficacy of intravitreal ranibizumab (RBZ) or conbercept in patients with wet age-related macular degeneration (wAMD) in a real-life setting in China. Methods: The medical records of 368 patients with wAMD who started RBZ or conbercept treatment between 1 May 2014 and 30 April 2018 were evaluated. All patients were defined on fundus angiography at baseline to determine the subtype of AMD (PCV or CNV). We report visual acuity (VA) and central retinal thickness (CRT) measurements at baseline and 12 months. Results: The average number of anti-VEGF injections was 2.1±1.2. The BCVA improvement of these two groups was similar with a difference of 1.00 letter (95% CI: -1.4~3.4, p=0.8505 ). At the end of the study, a BCVA increase of at least 5 letters was determined to be a satisfactory efficacy endpoint. Several factors were related to the possible improvement in the satisfactory efficacy endpoint, including female sex (OR 2.07, 95% CI 1.22~3.51), number of injections (OR 1.40, 95% CI 1.12~1.75) and VA change at the first month (OR 13.75, 95% CI 7.41~25.51). Additionally, some factors were related to the possible reduction in the satisfactory efficacy endpoint, including diabetes (OR 0.27, 95% CI 0.10~0.73) and disease history (OR 0.75, 95% CI 0.57~0.98). Conclusion: Our study demonstrates that anti-VEGF drugs can effectively improve BCVA and reduce CRT in AMD patients. Sex, number of injections, VA change at the first month, diabetes and disease history are the most important factors affecting visual acuity.